Device-level multi-rate electromagnetic transient simulation of power systems based on latency insertion method - Ding, Haoyin; Wang, Qiguo; Miao, Yuancheng; Cao, Lu; Yan, Zheng; Wang, Keyou (2022 7th Asia Conference on Power and Electrical Engineering (ACPEE), 2022)
In order to satisfy the demands of efficiency and accuracy of the electromagnetic transient (EMT) simulation of complex power systems, the paper proposes a device-level multi-rate electromagnetic transient simulation method based on the latency insertion method (LIM). The method takes the transmission grid as the upper layer modeling framework, and power electronics devices, synchronous generators, and other devices are connected to it in the form of controlled sources. Then, a natural decoupling network with the transmission grid as the main body and the rest of the equipment dispersed access is forming. Thus, the multiple time scale characteristics of various equipment in the power system can give full consideration, and the device-level multi-rate electromagnetic transient simulation can be realized by using different step sizes for different devices. Finally, this paper takes the improved IEEE-Case9 system as a case to prove the accuracy of the proposed multi-rate simulation algorithm and takes the cascade system of 10 improved IEEE-Case9 systems as a case to prove the efficiency of the multi-rate simulation algorithm.